"Words matter": Judicial discourse on domestic violence in China - D'Attoma, Sara (Comparative Legilinguistics, 2024)
The discourse about domestic violence focuses on power and control by the abuser among the victim through different means, one of those is the language. Besides the domestic walls within the abuses are perpetrated, a more institutional and usually regulated language on family violence is traceable in the public discourse, specifically in the People’s Court judgments. In cases regarding family matters, especially divorce proceedings, Chinese judges do often use paternalistic and educational language towards the couple. The aim of this paper is to carry out a preliminary research and analysis on the judicial discourse about domestic violence in order to evaluate to what extent, how and whether these paternalistic and educational nuances emerge in the language and statements used by judges in those cases. This research will be carried out firstly by building a corpus of judgments on “domestic violence” issues, and then by comparing data and analysing the specific language used by the authority using digital tools.